PERANCANGAN DAN IMPLEMENTASI SISTEM MONITORING KOGNITIF DAN AFEKTIF SISWA BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Ahmad Baihaqi; Resti Amalia (CV. Multi Kreasi Media, 2023)
Mis.Nurul Hidayah is an elementary school that still really needs expansion in the field of data integration, this school has been very long established, but there are still many processes that are carried out manually, one of which is in the process of assessing cognitive and affective monitoring of students, so it takes a long time in the process of monitoring the student, and also the frequent occurrence of damaged or corrupted files in the data of the results of the student monitoring assessment. By building this student monitoring system, it can help teachers in the process of accelerating the student monitoring assessment process and can also make better data integration in Mis.Nurul Hidayah. This system will be developed with the Rapid Application Development (RAD) method and implemented by using Unified Modeling Languange (UML), php and Mysql. The results of this research in the form of cognitive and affective monitoring of students are expected to be well implemented by teachers and school staff in order to make it easier for teachers in the process of assessing cognitive and affective monitoring of students to be used as reference material for student evaluation at the end of a meter.